Система передачі криптографічних ключів - Гнатюк, Сергій (Видавництво Національного університету «Львівська політехніка», 2009)
The proposed system of cryptography key distribution refers to the cryptographic protection of information and can be used for secure cryptographic key distribution for they further use in encruption algorithm. The technical effect can be achieved by implementation of this system and the point is to exclude the possibility of cryptographic key interception during the process of key transmission between stations. This introduced cryptography key distribution system is build to solve the problem of secure keys by using quantum key distribution key distribution which is based on inviolability of laws of quantum mecanics.
Keywords: protection; information security; quantum key distribution; secret key cryptography; Heisenberg uncertainty principle; Advanced Encryption Standard; the problem of key distribution; analog-to-digital converter